Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan Kabupaten dan Kota Provinsi Sulawesi Selatan - Suryati Suryati; Muhammad Syukri (Jurnal Varian, 2019)
The purpose of this study is to analyze the factors that influence the poverty rates in the Regencies and Cities of South Sulawesi Province. This type of research is applied research with secondary quantitative data. The data used in this study are secondary data obtained by the Central Statistics Agency (BPS) including population data; PDRB per capita; AMH, AHH, and the poverty rates of Regencies and Cities in South Sulawesi in 2019. Based on the results of the study it can be concluded that the population, per capita GRDP, AMH and AHH simultaneously affect the poverty rates of Regencies and Cities in South Sulawesi. Whereas, partially per capita GRDP variable and AMH variable significantly influence the poverty rates of Regencies and Cities in South Sulawesi. With the coefficient of determination each variable has a contribution to the poverty rate of 57.7% and the remaining 42.3% is influenced by other indicators not yet examined. The suggestions for the improvement and development of subsequent research is by adding other variables that can affect poverty rates. With the hope that there will be efforts from all parties, especially the local government, to present superior programs, for example the UMKM development program that can reduce poverty and have an impact on people's welfare.